2019
DOI: 10.1177/2473011419s00271
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Osteochondral Lesions of the Tibial Plafond Following Arthroscopic Microfracture

Abstract: Category: Ankle, Arthroscopy Introduction/Purpose: There is little data regarding osteochondral lesions of the tibial plafond with only a few studies reporting clinical outcomes after arthroscopic treatment. The purpose of this study is to evaluate the clinical outcomes and the level of sports activities following arthroscopic microfracture for osteochondral lesions of the tibial plafond. Methods: A retrospective review was conducted for all patients who underwent arthroscopic microfracture surgery for ankle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Ten articles were included in the review (Figure 1, Table 1). 2,3,5,10,13,18,20,24,29,36 All studies were published in 2000 or later and were deemed level 4 evidence, except for Elias et al 15 The mean Methodological Index for Non-randomized Studies score of the 5 surgical treatment studies 3,12,23,27,33 was 8.6 (range, 8-10); each of these was a noncomparative case series.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten articles were included in the review (Figure 1, Table 1). 2,3,5,10,13,18,20,24,29,36 All studies were published in 2000 or later and were deemed level 4 evidence, except for Elias et al 15 The mean Methodological Index for Non-randomized Studies score of the 5 surgical treatment studies 3,12,23,27,33 was 8.6 (range, 8-10); each of these was a noncomparative case series.…”
Section: Resultsmentioning
confidence: 99%
“…12,23,33 Cuttica et al 12 noted a return to unrestricted activity 20.9 ± 9.7 weeks after microfracture, with those with isolated lesions returning 4.1 weeks earlier compared with those with coexisting lesions (19.7 ± 9.2 vs 23.8 ± 11.7 weeks). This time frame was shorter than the mean 6.3 months (range, 2-22 months) for return to activity reported by Ross et al 33 Lee et al 23 found significant improvements in the Foot and Ankle Ability Measure-Sports subscale (from 34.5 ± 26.0 to 65.2 ± 30.2; P < .001) and reported 100% return to sports; however, they also noted a significant decrease in level of sports activity as defined by impact, with a larger proportion of patients performing lower-impact activity postoperatively (from 12.5% preoperatively to 62.5% postoperatively; P ¼ .012). Future studies evaluating return-to-sports outcomes after OLTPs should incorporate details on the type of sports, the level of activity, patient satisfaction with activity level or performance, and timing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Previous studies have reported a mean FAAM ADL score of 82.4 to 84.3 and a mean FAAM Sports score of 63.4 to 89.3 at least 12 months following surgery for osteochondral lesions with microfracture surgery, autograft, or allograft. 1,2,5,15 At least 24 months following TAR, studies have reported a mean FAAM ADL score of 81.7 to 82.2 and a mean FAAM Sports score of 57.3 to 59.5. 18,22 Following AA, the FAAM ADL and the FAAM Sports scores were 71.3 to 74.9 and 43.4 to 53.5, respectively.…”
Section: Discussionmentioning
confidence: 99%